Longitudinal Diagnostic Reassessment of Schizoaffective Disorder in Chronic Psychosis: A Case Report - Tegar Narindra Putra; Hafid Algristian; Miftakhul Huda (Indonesian Scientific Publication, 2026)
Differentiating schizophrenia from schizoaffective disorder remains a significant diagnostic challenge due to substantial symptom overlap and reliance on cross-sectional assessment. This case illustrates how systematic longitudinal reconstruction of mood symptom trajectories supported diagnostic revision after prolonged treatment under an initial schizophrenia diagnosis. A descriptive clinical case approach was employed, involving comprehensive patient interview, collateral family interview, longitudinal symptom mapping, and reassessment based on DSM-5-TR criteria. The patient was a 33-year-old woman with a 13-year history of chronic psychosis initially diagnosed as paranoid schizophrenia. Retrospective reconstruction identified five recurrent major depressive episodes lasting approximately 6–12 months each, accounting for an estimated 6–7 years of the illness course. In addition, at least one documented period of persistent psychosis lasting more than two weeks occurred in the absence of mood symptoms, fulfilling DSM-5-TR criteria for schizoaffective disorder, depressive type. Following diagnostic revision, antidepressant augmentation and structured psychosocial intervention were initiated. At three-month follow-up, depressive symptoms decreased, passive suicidal ideation resolved, and functional status improved as measured by the Personal and Social Performance (PSP) scale (from 40 to 60), with no rehospitalization. This case underscores the importance of longitudinal assessment in chronic psychosis and highlights its implications for diagnostic accuracy and treatment planning.